KEEFEKTIFAN PERMAINAN WORDWALL DALAM KETERAMPILAN BERBICARA MATERI SINONIM DAN ANTONIM SISWA KELAS V SDI AL MADINA - Wita Ermayanti; Ngatmini (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The purpose of this research is to improve students' speaking skills regarding fifth grade synonyms and antonyms by using the Wordwall game. This research uses a quantitative method with a True Experimental Design in the form of a pretest-posttest Control Group Design. The data analysis technique uses the t-test on posttest scores. With learning outcomes supported by static calculations after the Indonesian language learning process to improve students' speaking skills in the experimental class and Indonesian language learning experienced a slight increase in the control class. It can be seen that the final conditions of student learning outcomes are different. Through the t-polled variant test, it is proven that the t-count is 2.566 > t-table 2.021, so h0 is rejected and Ha is accepted, meaning that it can be said that the effectiveness of the Wordwall Game in Speaking Skills on Synonymous and Antonym Material for Class V Students of SDI Al Madina.